PENERAPAN SUPERVISI AKADEMIK UNTUK MENINGKATKAN KOMPETENSI PENDIDIK MENYUSUN ADMINISTRASI PENILAIAN DI MA YPK CIJULANG - Mulyana (Kantor Kementerian Agama Kabupaten Pangandaran bekerja sama dengan Asosiasi Profesi Perkumpulan Manajer Pendidikan Islam (Perma Pendis) Indonesia., 2020)
This study aims to improve the pedagogical competence of educators at Madrasah Aliyah Yayasan Pendidikan Kalangsari (YPK) Cijulang, Pangandaran Regency in preparing the administration of assessments through academic supervision. The method used in this research is school action research. The stages of activity in this research consisted of the stages of planning the action, implementing the action, observing, and reflecting. Data collection techniques using class observation techniques. The observation instrument used was the Educator Ability Assessment Tool (APKG) in the form of a learning administration assessment instrument. The data analysis used a comparative descriptive analysis technique. The quantitative data obtained were described in the form of words or explanations. Furthermore, data comparisons are carried out to ensure whether there is an increase in the ability of educators in assessing learning administration. The results showed that academic supervision could improve the ability of educators in compiling administrative assessments in learning at Madrasah Aliyah YPK Cijulang by 26.2%.